OUTCOME OF PATIENT SAFETY CULTURE USING THE HOSPITAL SURVEY ON PATIENT SAFETY CULTURE (HSOPSC) IN ASIA: A SYSTEMATIC REVIEW WITH META ANALYSIS - Rizky Anggraita Damayanti; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Patient safety is a critical component of the quality of health care. In the process, it allows health services, especially hospitals, to well understanding aspects of patient safety. Hospital Survey on Patient Safety Culture (HSOPSC) was established to examines patient safety culture and the correlation between patient safety culture composite hospitals in Asia. This study aims to assess patient safety culture which using Hospital Survey on Patient Safety Culture (HSOPSC). Methods: Systematic Review and meta-analysis method by using PRISMA-P 2015 were used in this study. We were collected through searching electronic literature from Elsevier, Science Direct, PubMed, and Google Scholar by using keywords